Antioxidant properties of red delicious apples as influenced by harvest dates, pre-treatments and storage conditions - Ganai, Shaiq Ahmad; Ahsan, Hafiza; Dar, Aamir Hussain; Allali, Farhana; Wani, S M (Journal of Postharvest Technology, 2019)
The objective of this study was to investigate the effect of harvest dates and postharvest treatments (precooling, calcium chloride and wax coating) on physical properties of apple cv Red delicious during storage. Fruits from three harvest dates (H1, H2 and H3) were subjected to various treatments include T1 (shade cooling), T2 (Hydrocooling), T3 (Hydrocooling+ calcium chloride), T4 (Hydrocooling + wax) and T5 (Hydrocooling + calcium chloride + wax) and were stored under ambient and refrigerated conditions for 100 days. All the treatments showed significant effect on anthocyanin, ascorbic acid and phenolic content. The harvest date H3 showed the maximum anthocyanin (33.30 mg/100g) and ascorbic content (12.50 mg/100g), Whereas polyphenolic content observed maximum in H1 (2.80 mg/100g). Among the treatments T5 showed the highest anthocyanin, ascorbic acid and phenolic content of 34.90 mg/100g, 12.50 mg/100g and 2.66 mg/100g, respectively. However, the anthocyanin content, ascorbic content and phenolic content were more decreased during ambient as compared to refrigerated storage.